ChemInform Abstract: Two‐Dimensional Transition‐Metal Electride Y2C. Issue 6 (23rd January 2015) - Zhang, Xiao; Xiao, Zewen; Lei, Hechang; Toda, Yoshitake; Matsuishi, Satoru; Kamiya, Toshio; Ueda, Shigenori; Hosono, Hideo
Abstract Polycrystalline layered Y2C with quasi‐2D anionic electrons confined in the interlayer is prepared by melting stoichiometric amounts of Y shots and C granules under Ar.